(untitled) (TAMADDUN NURI JURNALI, 2024)
Ethnolinguistics is a branch of science that studies the relationship between language and ethnicity. Ethnolinguistic research on the materials of the Slavic languages ​​is aimed at studying the culture, customs, historical development and peculiarities of the language of the Slavic peoples. Slavic languages, on the other hand, are a group of languages ​​with a widespread and rich history. They include Russian, Ukrainian, Belarusian, Polish, Czech, Slovak, Bulgarian, Serbian, Croatian and other languages. Each of these languages ​​has its own ethnolinguistic features, the study of which helps to better understand the culture and history of the Slavic peoples.